Analisis Optimalisasi Anggaran Penjualan dalam Peningkatan Kinerja Perusahaan - Amran Hotman Saragih; Asmawati Asmawati; Casria Sidabalok (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
Operational budget is a budget to prepare corporate income, where operating budget consists of revenue and expenditure for the company itself mendaptkan a net profit corporation. So also in this study aims to provide an overview of the implementation of the budget as a tool of management control in PDAM Pematangsiantar. The company has established operating budget is quite relevant in accordance with the previous year's evaluation to benchmark maketh ato size for a specified budget. Where the income and expenses incurred in 2011 and 2012 looks a distinguish between the realization set budget. It is caused by the presence of certain programs that have not been fully terlakasna and other factors such as inflation and rising budgetary capacities and volumes that were previously budgeted smaller apparently greater realization. So this led to an increase in budget and affect the realization